The Paradigm of the Musharakah Mutanaqishah Contract: Between Theory and Practice - Umam, Syafiul; Ahmad, Zakiyyah Ilma; Santoso, Muhammad Syafi'i Budi; Abidin, Ahmad Zainul (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2025)
Background. The Musyarakah Mutanaqishah (MMQ) contracts have become one of the leading products in the global Islamic Banking industry, especially for financing long-term assets such as property, vehicles, and as a refinancing scheme. Aim. Its partnership-based concept is considered to better represent the principles of fairness and risk-sharing than debt-based contracts. However, in its implementation, various challenges and debates have arisen regarding the compatibility of the theoretical framework in Islamic jurisprudence with practices in Islamic financial institutions (IFIs). Methods. This qualitative research aims to examine the theoretical paradigm of the MMQ contract, analyze its practical application in Indonesian Islamic Banking, and identify potential gaps between the two. Using a literature review and field study approach through document analysis and in-depth interviews with practitioners, this study found that while conceptually MMQ offers a true partnership scheme, its practice often exhibits tendencies closer to lease-based (ijarah) or debt-based (murabahah) financing models. Results. Gap This seen the more clear in application refinancing scheme, the structure of which can cause debate jurisprudence related ban on bai’ al-’inah. Gaps This identified in aspects ownership assets, mechanisms distribution risks and benefits, as well as structure contract dual (hybrid contract). Implications touch aspect sharia compliance, protection consumers, and challenges regulation. Research This recommend the need strengthening framework regulation, innovation more products substantial, as well as improvement literacy for practitioners and clients for ensure MMQ implementation in line with maqashid sharia.